P45 The patient perspective: using 'expert patient' feedback to improve simulation. (5th November 2017) - Hine, TS; Major, D; Purva, M; Wright, D
Abstract : Background: First defined by the chief medical officer in 2001, 'expert patients' are those 'who have the confidence, skills, information and knowledge to play a central role in the management of life with chronic diseases'. 1 It is currently rare for simulation courses to involve patients in their design and delivery. This is despite one of the major tenets of simulation being improvement in the quality and safety of patient care. We describe our experiences establishing the programme, as a work in progress. Methodology: The Hull Institute of Learning and Simulation (HILS) asks expert patients to attend simulation courses to provide patient-focussed feedback. Expert patients go through a standardised training package before attending. We created a feedback tool with sections for the scenario, debriefing, candidate and global perception of educational utility. In doing so we considered the local demand for greater patient engagement. Their observations are collected in real-time during simulation using the tool, with each domain scored on a 5-point Likert scale (Table 1). Scenario and debriefing feedback is provided directly to faculty, whilst feedback on the candidate is reviewed and used by trained faculty as part of the debrief. Results: We are collecting data on usability of the tool and acceptability of the programme to learners and faculty. Early experience has been positive. Conclusions and Recommendations: Patients are currently infrequently involved in the design, evaluation and continuing development of simulation training. It is therefore difficult to know whether courses meet their needs and expectations in relation to improving quality and safety of care. Quantifying the impact of this programme on course development is likely to prove challenging. However, once embedded, we should perhaps consider expert patients as core simulation faculty, welcoming their contribution to development in the usual iterative manner. References: . Department of Health. The expert patient: A new approach to chronic disease management in the 21st century 2001. London: Stationery Office.